Proceedings of the International Conference on Communication and Signal Processing 2016 (ICCASP 2016) 2017
DOI: 10.2991/iccasp-16.2017.16
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into Wire Electro-discharge Machining of A6061/Al2O3p Composites

Abstract: Abstract:Wire electrical discharge machining (WEDM) is a widely employed non-traditional machining process. Metal Matrix Composites (MMCs) are newly developed materials having favourable mechanical properties like high strength, hardness, wear resistance and strength to weight ratio. In this study, experimental investigation based on the Taguchi method involving four control factors with three levels using orthogonal array L18 is reported. Taguchi orthogonal array was used to study the effect of combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Baisane et al [26] found the higher surface roughness and lower material removal rate under the consideration of Al2O3p. Taguchi method is used during the machining of composite materials.…”
Section: Cutting Tool Techniques Based On Surface Structuringmentioning
confidence: 98%
“…Baisane et al [26] found the higher surface roughness and lower material removal rate under the consideration of Al2O3p. Taguchi method is used during the machining of composite materials.…”
Section: Cutting Tool Techniques Based On Surface Structuringmentioning
confidence: 98%